2018
DOI: 10.1007/s00418-018-1680-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of the epithelial-to-mesenchymal transition (EMT) in diseases of the salivary glands

Abstract: The link between inflammatory microenvironment and cancer emerged in the last years as a decisive factor in the induction of the pathological epithelial-mesenchymal transition (EMT). The EMT induces changes of cell states converting the epithelial cells to mesenchymal cells when this program is fully executed and EMT has emerged as a central driver of tumor malignancy. Cellular pathways activated by chronic inflammation brought about by chronic infections, by immune-mediated diseases, or by dysregulated wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 181 publications
(210 reference statements)
1
30
0
Order By: Relevance
“…Recently, the expression of CEACAM1 was shown to positively correlate with the expression of factors that are related to epithelial-mesenchymal transition (EMT) (Yoshikawa et al 2017). During pathological fibrosis following radiation therapy, healthy salivary acinar cells undergo a partial EMT and differentiate into a fibroblast-like phenotype (Hall et al 2010;Sisto et al 2018). Therefore, the extension of CEACAM1 membrane localization to the basal side of surviving acinar epithelial cells could indicate, on the one hand, an increased interaction of these cells with the extracellular matrix (ECM) but on the other hand also an EMT process induced by IR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the expression of CEACAM1 was shown to positively correlate with the expression of factors that are related to epithelial-mesenchymal transition (EMT) (Yoshikawa et al 2017). During pathological fibrosis following radiation therapy, healthy salivary acinar cells undergo a partial EMT and differentiate into a fibroblast-like phenotype (Hall et al 2010;Sisto et al 2018). Therefore, the extension of CEACAM1 membrane localization to the basal side of surviving acinar epithelial cells could indicate, on the one hand, an increased interaction of these cells with the extracellular matrix (ECM) but on the other hand also an EMT process induced by IR.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we detected the expression level of P-mTOR in salivary glands from embryonic stage to ICR mice at P1stage (Figs 1E and 9G). In the progression of salivary gland carcinoma, activation of mTOR, AKT and epithelial-to-mesenchymal transition (EMT) were seen in adult humans [66][67][68][69]. This phenomenon is similar to the activation of mTOR and AKT (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…However, there was only a 50% decrease in the expression level of P-mTOR, and P-S6K1 was not detected. In the progression of salivary gland carcinoma, activation of mTOR, AKT and epithelial-to-mesenchymal transition (EMT) were seen in adult humans [66][67][68][69]. This result showed that rapamycin selectively inhibits the mTORC1 signalling pathways without affecting mTORC2 during in vivo salivary gland development.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study reported that ongoing EMT may result in the progression of numerous diseases, such as cancer ( 36 ) and chronic kidney disease ( 37 ), particularly in CRSwNP ( 1 ). Following injury, the expression of junctional proteins, including E-cadherin, are downregulated and the expression of mesenchymal proteins, such as α-SMA, vimentin and fibronectin, are upregulated in epithelial cells, which then undergo EMT and alter morphology ( 38 ). In accordance with previous studies, the present study suggested that E-cadherin expression was reduced, while expression of α-SMA, vimentin and fibronectin were increased in CRSwNP and CRSsNP tissues compared with control groups.…”
Section: Discussionmentioning
confidence: 99%